2021
DOI: 10.1038/s41598-021-95602-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue oxygenation guided therapy and outcome in non-traumatic subarachnoid hemorrhage

Abstract: Brain hypoxia can occur after non-traumatic subarachnoid hemorrhage (SAH), even when levels of intracranial pressure (ICP) remain normal. Brain tissue oxygenation (PbtO2) can be measured as a part of a neurological multimodal neuromonitoring. Low PbtO2 has been associated with poor neurologic recovery. There is scarce data on the impact of PbtO2 guided-therapy on patients’ outcome. This single-center cohort study (June 2014–March 2020) included all patients admitted to the ICU after SAH who required multimodal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…Unklar ist allerdings, ob therapeutische Maßnahmen, die sich aus dem PbtO 2 -Monitoring ableiten, zu einer Verbesserung des klinischen Outcomes führen. In einer monozentrischen retrospektiven Studie wurden Maßnahmen, Komplikationen und Outcome verglichen zwischen einer ICP-gesteuerten Therapie ( n = 48) und einer ICP/PbtO 2 -gesteuerten Therapie ( n = 54; [ 9 ]). Ein Großteil (87 %) der Patienten mit PbtO 2 -Sonde wiesen mindestens eine detektierte hypoxische Phase auf.…”
Section: Neues Zum Monitoring Der Aneurysmatischen Subarachnoidalblutungunclassified
“…Unklar ist allerdings, ob therapeutische Maßnahmen, die sich aus dem PbtO 2 -Monitoring ableiten, zu einer Verbesserung des klinischen Outcomes führen. In einer monozentrischen retrospektiven Studie wurden Maßnahmen, Komplikationen und Outcome verglichen zwischen einer ICP-gesteuerten Therapie ( n = 48) und einer ICP/PbtO 2 -gesteuerten Therapie ( n = 54; [ 9 ]). Ein Großteil (87 %) der Patienten mit PbtO 2 -Sonde wiesen mindestens eine detektierte hypoxische Phase auf.…”
Section: Neues Zum Monitoring Der Aneurysmatischen Subarachnoidalblutungunclassified
“…For example, Hosmann et al (2022) define indications for cerebral ischemia as CMD L/P-ratio >40 CMD-glycerol >100 μmol/L, CMD-lactate >4 mmol/L, whereas Nyholm et al (2017) defined cerebral ischemia as CMD-L/P ratio >40 and CMD-pyruvate <50 mol/L). For brain tissue hypoxia monitored by PbtO 2 there were in general two definitions used: PbtO 2 <15 mmHg ( Burnol et al, 2021 ; Hosmann et al, 2021 ) or <20 mmHg ( Le Roux et al, 2014 ; Gagnon et al, 2020 ; Sekhon et al, 2020 ; Gouvea Bogossian et al, 2021 ).…”
Section: Results Objective Ii: Secondary Injuriesmentioning
confidence: 99%
“…of studies References ABP-management Arterial blood pressure-management 4 (Jakkula et al, 2018;Calviello et al, 2019;Sekhon et al, 2019;Kovacs et al, 2021) b Biomarkers Neuroglobin, prostacyclin, succinate 3 (Ding et al, 2019;Koskinen et al, 2019;Khellaf et al, 2022) a Fluid management CSF drainage, hypertonic saline, and/or fluid management 5 (Akbik et al, 2017;Carteron et al, 2018;Hoiland et al, 2021;Rass et al, 2021;Bernini et al, 2022) Mixed interventions Nimodipine, ICP/CPP management (vasopressors, sedation, etc. ), hyperoxia, glucose, head elevation/flat position 11 (Bele et al, 2015;Lin et al, 2015;Okonkwo et al, 2017;Sekhon et al, 2017;Rass et al, 2019;Veldeman et al, 2020a;Veldeman et al, 2020b;Fergusson et al, 2021;Gouvea Bogossian et al, 2021;Khellaf et al, 2022;Winberg et al, 2022) a…”
Section: Intervention Group Interventionsmentioning
confidence: 99%
“…The value of adjusting hemodynamic and ventilator parameters based on brain tissue oxygen (PbtO 2 ) is being investigated. Observational studies in TBI and SAH have shown higher mortality in association with decreased PbtO 2 levels and suggested outcome benefits with PbtO 2 -directed therapy [53][54][55][56][57][58]. The Brain Oxygen Optimization in Severe TBI (BOOST-3) trial, a phase 3 RCT, is assessing the potential to improve neurological outcomes in TBI by comparing ICU care guided by ICP monitoring only against an ICP plus PbtO 2 -guided management strategy [59].…”
Section: Mechanical Ventilation Targets In Sabimentioning
confidence: 99%